3D RECONSTRUCTION OF CITRUS TREES USING AN OMNIDIRECTIONAL OPTICAL SYSTEM - Castanheiro, L. F. [UNESP]; Tommaselli, A. M. G. [UNESP]; Campos, M. B.; Berveglieri, A. [UNESP]; Santos, G. [UNESP]; IEEE (Ieee, 2020)
This paper presents a feasibility study on the use of omnidirectional systems for 3D modelling of agricultural crops, aiming a systematic monitoring. Omnidirectional systems with multiple sensors have been widely used in close-range photogrammetry (CRP), which can be a good alternative to provide data for digital agriculture management. The GoPro Fusion dual-camera is the omnidirectional system used in this work. This system is composed of two cameras with fisheye lenses that cover more than 180 degrees each one in back-to-back position. System calibration, camera orientation and 3D reconstruction of an agricultural cultivated area were performed in Agisoft Metashape software. A 360 degrees calibration field based on coded targets (CTs) from Agisoft Metashape software was used to calibrate the omnidirectional system. The 3D reconstruction of an orange orchard was performed using fisheye images taken with GoPro Fusion. The results show the potential of using an omnidirectional system for 3D modelling in agricultural crops, in particular citrus trees. Interior orientation parameters (IOPs) was estimated using Agisoft Metashape target/software with a precision of 9 mm. A 3D reconstruction model of the orange orchard area was obtained with an accuracy of 3.8 cm, which can be considered acceptable for agricultural purposes.
Keywords: Digital agriculture; orange orchard; poly-dioptric system; fisheye lens; dual-camera; terrestrial mapping; camera calibration; 3D tree modelling